Resources to Advantage: An Integrated Conceptual AnalysisOf VRIN ‎and VRIO Frameworks in Strategic Management - Antony, Angel Clare; P.S , Dr. Anuradha. (International Journal of Accounting and Economics Studies, 2026)
The Resource-Based View (RBV) has long been recognized as a cornerstone of strategic ‎management, emphasizing the role of firm-specific resources in achieving sustainable ‎competitive advantage (SCA). Two prominent frameworks derived from RBV, VRIN and ‎VRIO, offer systematic approaches to evaluating resources based on Value, Rarity, ‎Inimitability, Non-substitutability (VRIN), and Organization (VRIO). This conceptual paper ‎critically examines the theoretical underpinnings, comparative distinctions, and strategic ‎implications of VRIN and VRIO frameworks. By integrating insights from both models, a ‎unified conceptual framework is proposed, elucidating the process through which resources are ‎transformed into sustained competitive advantage. The paper also identifies managerial ‎applications and highlights potential avenues for future research, particularly in dynamic and ‎technology-driven industries. This unified perspective is particularly relevant for firms operating ‎in dynamic industries requiring both resource uniqueness and adaptive organizational capacity. ‎The paper aims to bridge the gap between theoretical resource evaluation and actionable ‎strategy, offering an updated contribution to resource-based strategic management literature. ‎The study also contributes to the literature by providing a comprehensive, real conceptual analysis, ‎offering academics and practitioners a practical lens to evaluate and leverage organizational ‎resources effectively‎.
Keywords: Organizational Resources; Resource-Based View; Sustainable Competitive Advantage; VRIN ‎Framework; VRIO Framework